ANALISIS PENGENDALIAN MUTU PADA PENJUALAN IKAN BADER/TAWES METODE SQC DI TPI UD. JAZULI IB GRESIK - ROSYIDI, MOH RIRIN (Jurnal IPTEK, 2017)
UD. Jazuli IB in TPI Lumpur Gresik has implemented quality control. But in the belief, there is damage to bader/tawes in 2016 with a percentage of 17%. The purpose of this research is to know the implementation of quality control at UD. Jazuli IB in bader/tawes fishing and quality control system using statistical quality. Control approach with the result of this research is implementation of quality control in fish processing bader/tawes seen from good in meeting company standards, this is evidenced by customer statement when monitored using map control, quality control it some have not been properly implemented, as many damaged fish are out control limits quality control by using the quality cost implemented by the company is still loose, because the cost of quality issued to control the cost quality is 187,444,404 IDR, quality assurance fee 18,204,000 IDR, and total cost for quality 205,648,404 IDR with damage rate 1,517 kg, it is bigger than it should be quality cost. Costs for 58,414,320 IDR, and the total cost for the quality level is 116,828,715 IDR with the rate from damage 4,867.86 kg. Thus, companies need to improve quality continuously to obtain maximum results and processing and quality control.